Giles Chance, China and the Credit Crisis. The Emergence of a New World Order, Singapur, John Wiley & Sons (Asia) Pte. Ltd., 2010, 224 pp. - Fonseca Fernández, Fabricio Antonio (Estudios de Asia y África, 2011)
Giles Chance, China and the Credit Crisis. The Emergence of a New World Order, Singapur, John Wiley & Sons (Asia) Pte. Ltd., 2010, 224 pp.